Physical and mechanical properties of kenaf stems at varying moisture contents - Dauda, Solomon Musa; Ahmad, Desa; Abdan, Khalina; Othman, Jamarei (Elsevier, 2014)
Physical and mechanical properties of kenaf stem Malaysian variety V 36 were studied. The physical properties revealed maximum plant height was 310 cm and the lowest was 150 cm. Maximum stem diameter was 30 mm and the smallest was 14 mm. The mechanical properties revealed the maximum cutting force and shearing energy were 1584.55 N and 8.75 J, respectively for 35% moisture content. While 694.86 N and 3.50 J were recorded for 72% moisture content. The Young's modulus ranged between 67.59 MPa to 234.24 MPa. The greater shearing energy was obtained at the lower levels in the stem.